Individual-level employment transitions in rural Viet Nam - Ngo Quang-Thanh (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Structural transformation in rural areas is a key issue in economic development. While much of the literature on structural transformation has so far focussed on household- or commune levels or even higher aggregate levels, little is known about the individual member level. The paper aims at examining factors that affect the individual-level employment rural transitions in Viet Nam, namely: (1) non-transient farm; (2) positive transient farm; (3) out-of-wage transition; (4) transitory farm-household work; and (5) transitory wage-household work. By taking advantage of the Viet Nam Access to Resources Household Survey (VARHS) with data on 2,699 individuals for two years, 2008 and 2016, we find that individual-level human capital and social capital are important factors affecting employment transition status in the rural area. In addition, changes in individual and household characteristics and socio-economic conditions at commune level are important to influence various types of employment transitions. These results have implications for the development policy on rural transition in developing countries, highlighting the importance of recognizing the positive aspects of changes in individual-, household-, and commune-levels for rural transformation. Promotion of education attainment is necessary at both individual- and household-level to spur the transition out of farming. Broadened policy mechanisms which support and encourage non-farm employment at the household level are also needed. Likewise, development initiatives that focus on increasing the human and social assets of the individual farmers and farming households are more likely to be successful in supporting livelihood diversification and reducing vulnerability.
Keywords: Q12; C21; C26; C33; 330; individual-level employment transitions; rural; Viet Nam